2009
DOI: 10.2110/jsr.2009.092
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Genesis, and Distribution of Nanometer-Scale Pores in Siliceous Mudstones of the Mississippian Barnett Shale

Abstract: Research on mudrock attributes has increased dramatically since shale-gas systems have become commercial hydrocarbon production targets. One of the most significant research questions now being asked focuses on the nature of the pore system in these mudrocks. Our work on siliceous mudstones from the Mississippian Barnett Shale of the Fort Worth Basin, Texas, shows that the pores in these rocks are dominantly nanometer in scale (nanopores). We used scanning electron microscopy to characterize Barnett pores from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
1,365
4
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,432 publications
(1,410 citation statements)
references
References 24 publications
35
1,365
4
6
Order By: Relevance
“…Shales contain distinct phases of oil-wetting organic matter (e.g., kerogen) and water-wetting minerals, and tracers in two fluids (API brine and n-decane) are used to interrogate the wettability and connectivity of organic matter and mineral pore spaces. The organic fluid (n-decane) is expected to be preferentially attracted to the hydrophobic component (e.g., organic particles) of the shale matrix, with reported organic (kerogen) particle sizes ranging from less than 1 lm to tens of lm (Loucks et al 2009;Curtis et al 2012). Organic grains are found to be dispersed through the Barnett shale matrix (Hu and Ewing 2014), with their connection to mineral phases unknown.…”
Section: Spontaneous Fluid Imbibition and Tracer Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Shales contain distinct phases of oil-wetting organic matter (e.g., kerogen) and water-wetting minerals, and tracers in two fluids (API brine and n-decane) are used to interrogate the wettability and connectivity of organic matter and mineral pore spaces. The organic fluid (n-decane) is expected to be preferentially attracted to the hydrophobic component (e.g., organic particles) of the shale matrix, with reported organic (kerogen) particle sizes ranging from less than 1 lm to tens of lm (Loucks et al 2009;Curtis et al 2012). Organic grains are found to be dispersed through the Barnett shale matrix (Hu and Ewing 2014), with their connection to mineral phases unknown.…”
Section: Spontaneous Fluid Imbibition and Tracer Migrationmentioning
confidence: 99%
“…While the presence of nanopores in shales has been well recognized since the first application of Ar-ion milling and field-emission SEM imaging (Loucks et al 2009) to indicate the dominant organic nanopores in Barnett shales, larger pores cannot be discounted in their roles of mass transport and connecting nanopore regions. Pores less than 3 nm can be quantified with approaches such as lowpressure gas sorption isotherm, but such small pores probably do not play critical roles in hydrocarbon movement (Javadpour et al 2007).…”
Section: Mercury Intrusionmentioning
confidence: 99%
“…The experimental evaluation showed that the CH 4 adsorption capacity of shale increases with the increment of pressure (Cheng and Huang, 2004;Loucks et al, 2009;Lu et al, 1995;Bustin, 2007, 2008), implying that the high pressures in the actual shale gas reservoir might result in a large CH 4 adsorption amount. In contrast, high reservoir temperatures are unfavorable with respect to CH 4 adsorption and decrease the adsorption capacity of shale (Ross and Bustin, 2008;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Shale gas, which is derived from organic matters in shale and stored in shale deposits, is an important unconventional gas resource and has recently attracted attention for its promising exploitation (Chalmers and Bustin, 2008;Curtis, 2002;Jing et al, 2011;Loucks et al, 2009;Bustin, 2007, 2009;Zhang et al, 2012). Methane (CH 4 ) sourced from thermogenesis and/or biogenesis of organisms is the dominant component of shale gas (Hill et al, 2007;Strapoc et al, 2010;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation